Oncolytic virus driven T-cell-based combination immunotherapy platform for colorectal cancer - Crupi, Mathieu J. F.; Taha, Zaid; Janssen, Thijs J. A.; Petryk, Julia; Boulton, Stephen; Alluqmani, Nouf; Jirovec, Anna; Kassas, Omar; Khan, Sarwat T.; Vallati, Sydney; Lee, Emily; Huang, Ben Zhen; et al. (Frontiers in Immunology, 2022)
Colorectal cancer is the third most diagnosed cancer and the second leading cause of cancer mortality worldwide, highlighting an urgent need for new therapeutic options and combination strategies for patients. The orchestration of potent T cell responses against human cancers is necessary for effective antitumour immunity. However, regression of a limited number of cancers has been induced by immune checkpoint inhibitors, T cell engagers (TCEs) and/or oncolytic viruses. Although one TCE has been FDA-approved for the treatment of hematological malignancies, many challenges exist for the treatment of solid cancers. Here, we show that TCEs targeting CEACAM5 and CD3 stimulate robust activation of CD4 and CD8-positive T cells in in vitro co-culture models with colorectal cancer cells, but in vivo efficacy is hindered by a lack of TCE retention in the tumour microenvironment and short TCE half-life, as demonstrated by HiBiT bioluminescent TCE-tagging technology. To overcome these limitations, we engineered Bispecific Engager Viruses, or BEVirs, a novel tumour-targeted vaccinia virus platform for intra-tumour delivery of these immunomodulatory molecules. We characterized virus-mediated TCE-secretion, TCE specificity and functionality from infected colorectal cancer cells and patient tumour samples, as well as TCE cytotoxicity in spheroid models, in the presence and absence of T cells. Importantly, we show regression of colorectal tumours in both syngeneic and xenograft mouse models. Our data suggest that a different profile of cytokines may contribute to the pro-inflammatory and immune effects driven by T cells in the tumour microenvironment to provide long-lasting immunity and abscopal effects. We establish combination regimens with immune checkpoint inhibitors for aggressive colorectal peritoneal metastases. We also observe a significant reduction in lung metastases of colorectal tumours through intravenous delivery of our oncolytic virus driven T-cell based combination immunotherapy to target colorectal tumours and FAP-positive stromal cells or CTLA4-positive Treg cells in the tumour microenvironment. In summary, we devised a novel combination strategy for the treatment of colorectal cancers using oncolytic vaccinia virus to enhance immune-payload delivery and boost T cell responses within tumours.